Survival of Lactobacillus plantarum Encapsulated with Skim Milk and Arabic Gum after Spray Drying and Its Viability during Storage - Rizqiati, H; Jenie, BSL; Nurhidayat, N; Nurwitri, C (ANIMAL PRODUCTION, 2008)
Ten isolates of Lactobacillus plantarum were selected for its survival after heating. Two isolates which showed the highest survival rate were then encapsulated with skim milk, Arabic gum and mixtured of skim milk - Arabic gum. The probiotic cultures were prepared in the form of suspension and biomass and then spray dried. Survival of the probiotic encapsulated in the form of biomass after spray drying, and the viability after one month of storage at room temperature were higher than the suspension. It was found that the survival of probiotic bacteria in different encapsulation materials varied after spray drying. The number of probiotic survivals decreased after spray drying for all encapsulation materials tested ranged from less than 1 log cycle to 2 log cycles. Encapsulation of probiotic with three types combination of encapsulating materials showed that no significant difference of survivals after spray drying and viability after one month of storage were observed. The remained number of the probiotic after one month of storage at 4oC and room temperature was 104-107 cfu/gand 102-105 cfu/g, respectively. (Animal Production 10(3): 179-187 (2008) Key Words: Encapsulation, probiotic, skim milk, Arabic gum